Sources of the Levantine Intermediate Water in Winter 2019. Issue 6 (24th June 2022) - Taillandier, V.; D'Ortenzio, F.; Prieur, L.; Conan, P.; Coppola, L.; Cornec, M.; Dumas, F.; Durrieu de Madron, X.; Fach, B.; Fourrier, M.; Gentil, M.; Hayes, D.; et al.
Abstract: Climatic changes and interannual variability in the Mediterranean overturning circulation are crucially linked to dense water formation in the Levantine Sea, namely the Levantine Intermediate Water whose formation zone, comprising multiple and intermittent sources, extends over fluctuating pathways. To probe into the variability of this water formation and spreading, a unique dataset was collected during the winter of 2019 in the western Levantine Sea, via oceanographic cruises, profiling floats and a glider, at a spatio‐temporal distribution suited to resolve mesoscale circulation features and intermittent convection events. This study highlights the competition between two source regions, the Cretan Sea and the Rhodes Cyclonic Gyre, to supply the Mediterranean overturning circulation in Levantine Intermediate Water. The Cretan source was estimated as the most abundant, supported by increasingly saltier water masses coming from the Levantine Sea under the pumping effect of a water deficit caused by strong western outflow toward the Ionian Sea. Plain Language Summary: The Mediterranean overturning circulation is a conveyor belt transporting salt from its easternmost areas toward the North Atlantic Ocean. To explore how the formation of dense and salty waters called the Levantine Intermediate Water fits into this circulation, the western Levantine Sea was investigated during the winter of 2019 via cruise surveys and an array of autonomous sensors. This study highlights the competition between two source regions, the southern Aegean Sea and the northwestern Levantine Sea, to supply the Mediterranean overturning circulation in Levantine Intermediate Water. In the period under study, the first region was estimated as the most abundant source. This source was supported by increasingly saltier water masses coming from the Levantine Sea, under the pumping effect of a water draught in the Aegean Sea. These observations help to nuance the complex picture of Levantine circulation patterns which are subject to large variability. Key Points: Descriptive oceanography of the Levantine Intermediate Water formation zone using an in‐situ multiplatform approach Competition between two source regions to supply the Mediterranean overturning circulation in Levantine Intermediate Water The Cretan Sea is the most abundant source, supported by increasingly saltier waters coming from the Levantine Sea